Analisis Prevalensi dan Intensitas Pseudorhabdosynochus coioidesis Pada Ikan Kerapu Bebek (Cromileptes altivelis) di Perairan Lampung dan Situbondo - Hervina Benazir Ardiyanti; Sri Subekti; Kusnoto (Airlangga University, 2022)
Humpback Groupers (Cromileptes altivelis) are a type of fish with great economic value that has the potential to be developed in Indonesia. Pseudorhabdosynochus coioidesis is one of the species that has been documented to infest Humpback Groupers. The purpose of this study was to determine the prevalence and severity of the parasitic worm Pseudorhabdosynochus coioidesis in Humpback Groupers in Lampung and Situbondo seas. 75 Humpback Groupers (20-35 cm) were sampled from Lampung waters, and 60 from Situbondo seas. The data were processed descriptively and presented in tabular form. The results showed that there was Pseudorhabdosynochus coioidesis worm infestation on the gills of Humpback Groupers in Lampung and Situbondo waters. The prevalence value of Pseudorhabdosynochus coioidesis in Humpback Groupers in Lampung waters was 93% with the almost always category and the intensity value was 1.48 in the low category while in Situbondo waters the prevalence value was 95% with the almost always category and the intensity value was 1.33 with low category. The low-intensity result indicates that the presence of Pseudorhabdosynochus coioidesis is not as dangerous to crop yields, but it should still be monitored.